(322) تخطيط القوى العاملة Manpower planning - مختار حمزة (معهد التخطيط القومي, 2026)
ملخص تتناول هذه المذكرة البحثية التي أعدها الدكتور مختار حمزة عام 1963 أهمية القوى البشرية كركيزة أساسية لتخطيط التنمية الاقتصادية والاجتماعية، موضحة أن العائق الرئيسي للتقدم يكمن في نقص العمالة المدربة والمؤهلة. وتؤكد الدراسة أن مشكلة القوى العاملة لا تقتصر على جوانب التعليم والتدريب الفنية فحسب، بل هي قضية مجتمعية معقدة تتشابك فيها ميول الأفراد وقيم المجتمع نحو المهن المختلفة مع مستويات الأجور والمعايير الاقتصادية، مما يستلزم الاعتماد على إحصائيات سكانية وتربوية دقيقة لبناء التنبؤات المستقبلية اللازمة لتطوير الهيكل الوظيفي في قطاعات الزراعة والصناعة والخدمات. كما يستعرض الملف إطاراً علمياً للتخطيط يعتمد على التنبؤ بالتقدم الاقتصادي وتقدير معدلات الإنتاج وتطوير السلم الوظيفي، مع التشديد على ضرورة الموازنة بين عرض الخريجين والطلب الفعلي في سوق العمل. ويبرز التقرير تجارب دولية مقارنة للتأكيد على أهمية رسم سياسات تعليمية وتربوية متكاملة تتضمن تطوير المناهج وتوفير المعلمين والمباني المدرسية، لضمان تخريج كوادر وطنية قادرة على دفع عجلة النمو وبناء مجتمع حديث يتسم بالكفاءة الإنتاجية العالية. This research paper, prepared by Dr. Mukhtar Hamza in 1963, addresses the importance of human resources as a fundamental pillar for economic and social development planning, explaining that the main obstacle to progress lies in the shortage of trained and qualified labor. The study emphasizes that the labor force problem is not limited to aspects of education and technical training alone, but is a complex societal issue in which individual inclinations and societal values toward different professions are intertwined with wage levels and economic standards. This necessitates reliance on accurate demographic and educational statistics to build the future projections necessary for developing the job structure in the agricultural, industrial, and service sectors . The report also presents a scientific framework for planning based on forecasting economic progress, estimating production rates, and developing career paths, while emphasizing the need to balance the supply of graduates with the actual demand in the labor market. It highlights comparative international experiences to underscore the importance of developing integrated educational policies that include curriculum development, providing teachers and school buildings, to ensure the graduation of qualified national personnel capable of driving growth and building a modern, highly productive society .